The Tomato DELLA Protein PROCERA Promotes Abscisic Acid Responses in Guard Cells by Upregulating an Abscisic Acid Transporter - Shohat, Hagai (Plant Physiol, 2020)
Plants reduce transpiration through stomatal closure to avoid drought stress. While abscisic acid (ABA) has a central role in the regulation of stomatal closure under water-deficit conditions, we demonstrated in tomato (Solanum lycopersicum) that a gibberellin response inhibitor, the DELLA protein PROCERA (PRO), promotes ABA-induced stomatal closure and gene transcription in guard cells. To study how PRO affects stomatal closure, we performed RNA-sequencing analysis of isolated guard cells and identified the ABA transporters ABA-IMPORTING TRANSPORTER1.1 (AIT1.1) and AIT1.2, also called NITRATE TRANSPORTER1/PTR TRANSPORTER FAMILY4.6 in Arabidopsis (Arabidopsis thaliana), as being upregulated by PRO. Tomato has four AIT1 genes, but only AIT1.1 and AIT1.2 were upregulated by PRO, and only AIT1.1 exhibited high expression in guard cells. Functional analysis of AIT1.1 in yeast (Saccharomyces cerevisiae) confirmed its activity as an ABA transporter, possibly an importer. A clustered regularly interspaced short palindromic repeats-Cas9–derived ait1.1 mutant exhibited an increased transpiration, a larger stomatal aperture, and a reduced stomatal response to ABA. Moreover, ait1.1 suppressed the promoting effects of PRO on ABA-induced stomatal closure and gene expression in guard cells, suggesting that the effects of PRO on stomatal aperture and transpiration are AIT1.1-dependent. Previous studies suggest a negative crosstalk between gibberellin and ABA that is mediated by changes in hormone biosynthesis and signaling. The results of this study suggest this crosstalk is also mediated by changes in hormone transport.